A systematic review of the determinants of seafood consumption. Issue 1 (14th July 2021) - Govzman, S.; Looby, S.; Wang, X.; Butler, F.; Gibney, E. R.; Timon, C. M.
Abstract: Although seafood is considered to be an important part of a balanced diet, many national food consumption surveys suggest that seafood is not consumed in sufficient amounts. As consumers are moving to diversify their diet from animal-based protein, it is important to understand the factors influencing consumption of marine foods. This review aims to assess the characteristics of seafood consumers as well as the influences on seafood consumption in Europe, USA, Canada, Australia and New Zealand. Systematic search strategies were used to identify relevant journal articles from three electronic databases (PubMed, Web of Science and Embase). Three searches were carried out and identified 4405 unique publications from which 121 met the criteria for the review process. The reviewed studies revealed that seafood consumers were more likely to be older, more affluent and more physically active and were less likely to smoke compared with non-seafood consumers. Sex and BMI did not appear to have a directional association with seafood consumption. The most commonly reported barriers to seafood consumption were cost, followed by sensory or physical barriers, health and nutritional beliefs, habits, availability and cooking skills. The most commonly reported influences were beliefs about the contribution of seafood to health, environmental influences and personal preferences. Based on the findings of this review, future intervention strategies to increase seafood consumption may need to consider affordability and education in terms of health, nutrition and cooking skills. More research is needed to explore the effectiveness of specific interventions at increasing the consumption of seafood. Abstract :